MODEL SIMULASI ALUR PROSES PETI KEMAS IMPOR PADA PEMILIHAN LOKASI EXTERNAL YARD DI KAWASAN PENYANGGA PELABUHAN - Rusgiyarto, Ferry; Frazilla, Russ Bona; Sjafruddin, Ade; ., Suprayogi (Jurnal Transportasi, 2017)
AbstractÂ Increasing container flows and lack of land development for the container terminal, cause yard sub-functions are located in the port buffer area. This condition emerges additional transportation cost and causes traffic problems on the access road. This paper deals with simulation model construction which will be used to find optimum external yard configuration location in the port buffer area. Discrete Event Simulation Model will be used to simulate import container flow processes in the port container terminal. The Objective function of the external yard location model is to minimize user transport cost and to maximize operator benefit. Jakarta International Container Terminal data is used to construct the model. Model concept is run based on the scenario assumption of 3 TPSâs and 30 day simulation period. Based on three replicants and five times running, the optimum result is 3 TPSs simultaneously operation. The model needs detail elaboration in associated to model objective function and model optimization constraint. It is required detail validation, in term of service time value, distribution pattern and arrival rate in each unit server modelled in the next step of the research. Nevertheless, the model gives unique and relatively consistent result value of each trial. It is indicated that the method can be used to solve the research objective.Â Keywords: simulation model, import container, location model, external yardÂ Â AbstrakÂ Peningkatan arus peti kemas dan keterbatasan lahan terminal peti kemas menyebabkan beberapa subfungsi yard ditempatkan di kawasan penyangga pelabuhan. Kondisi ini menyebabkan tambahan biaya transportasi dan permasalahan lalulintas pada jalan akses. Makalah ini berkaitan dengan pembentukan model simulasi yang akan digunakan untuk menentukan lokasi optimum beberapa external yard di kawasan penyangga pelabuhan. Model Discrete Event Simulation digunakan dalam simulasi alur proses peti kemas impor. Fungsi tujuan model adalah minimasi biaya transportasi pengguna dan maksimasi keuntungan operator. Data peti kemas Jakarta International Container Terminal (JICT) digunakan untuk menyusun model. Konsep model dijalankan berdasarkan asumsi skenario tiga TPS dan 30 hari periode simulasi. Berdasarkan tiga replikasi dan lima percobaan running model, hasil optimum adalah pengoperasian tiga TPS bersamaan. Model perlu dielaborasi lebih lanjut terkait fungsi tujuan dan batasan model optimisasi. Diperlukan validasi rinci terhadap nilai waktu pelayanan, pola distibusi, dan tingkat kedatangan unit-unit pelayanan pada langkah selanjutnya dari penelitian. Walaupun demikian, model memberikan hasil yang unik dan relatif konsisten setiap percobaan. Hal ini mengindikasikan metode dapat digunakan untuk memecahkan tujuan penelitian.Â Kata-kata kunci: model simulasi, peti kemas impor, model lokasi, external yard